Professional Learning Communities for Strengthening Technology-Responsive Teaching Practices - Wulandari, Liyani; Wijayanti, Wiwik (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of digital technologies has transformed expectations of teachers' professional competence, requiring continuous learning, collaboration, and the integration of technology into instructional practices. This study aims to synthesize empirical evidence regarding the contribution of Professional Learning Communities (PLCs) to strengthening technology-responsive teaching practices through a Systematic Literature Review (SLR). The review followed the PRISMA framework, encompassing identification, screening, eligibility assessment, and final inclusion of relevant studies. From an initial pool of ten Scopus-indexed publications, six empirical open-access articles published between 2019 and 2025 met the predefined inclusion criteria. The synthesis demonstrates that PLCs consistently enhance teaching practices by promoting professional collaboration, reflective dialogue, collective learning, and supportive organizational conditions. Furthermore, PLCs facilitate teachers' readiness to integrate digital technologies into classroom instruction, improve instructional decision-making, and encourage adaptive pedagogical innovation in response to evolving educational demands. Several studies also indicate that PLCs strengthen the relationship between school leadership and teacher performance while fostering technology-supported professional learning environments. However, the effectiveness of PLC implementation depends on enabling factors such as collaborative leadership, positive school culture, teachers' growth mindset, and adequate technological infrastructure, whereas limited institutional support and insufficient digital readiness remain significant barriers. These findings position PLCs as a strategic techno-pedagogical approach for developing sustainable teacher professionalism and fostering technology-responsive teaching practices. The review provides implications for educational leaders and policymakers in designing collaborative professional development models that effectively support digital transformation in schools.